Pengaruh Sistem Hukum Dunia Terhadap Pembentukan Peraturan Perundang-Undangan di Indonesia - Rama Ahmad Raja Maranay; Irsyaf Marsal (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This article examines the influence of global legal systems on the formation of legislation in Indonesia. Historically, Indonesia adopted the Continental European legal system inherited from the Netherlands as the foundation of its national legal framework. Over time, Indonesia’s legal system has also been shaped by principles of common law, Islamic law, and customary law, deeply rooted in the nation's culture. This study aims to analyze how the interplay of these diverse legal systems has contributed to the development of a unique and complex national legal structure. Employing a literature review and normative analysis method, the research explores how elements from various global legal systems have enriched Indonesia’s legal framework. The findings reveal that, while this diversity enhances the national legal system, it also presents challenges in harmonizing and synchronizing existing regulations. This study offers valuable insights into the dynamics of cross-system legal influences in the Indonesian context and their implications for national legal reform.